2.9=(n-3.4)/4

Simple and best practice solution for 2.9=(n-3.4)/4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.9=(n-3.4)/4 equation:



2.9=(n-3.4)/4
We move all terms to the left:
2.9-((n-3.4)/4)=0
We multiply all the terms by the denominator
-((n-3.4)+(2.9)*4)=0
We calculate terms in parentheses: -((n-3.4)+(2.9)*4), so:
(n-3.4)+(2.9)*4
We add all the numbers together, and all the variables
(n-3.4)+11.6
We get rid of parentheses
n-3.4+11.6
We add all the numbers together, and all the variables
n+8.2
Back to the equation:
-(n+8.2)
We get rid of parentheses
-n-8.2=0
We add all the numbers together, and all the variables
-1n-8.2=0
We move all terms containing n to the left, all other terms to the right
-n=8.2
n=8.2/-1
n=-8+0.2/1

See similar equations:

| -8(3/2x+1)=-101 | | 2x-1=3/4x-7 | | -17z-20=16-15z | | -5(5b+7)=7b+29 | | 2(-x+3)=-(2x-6) | | 17-11r+7=-15r-12 | | 18=10x-3(5x-7)+8x | | .25x=50+.15x | | -7t=17-8t | | 6.7x=5.2x+12.3=12.9 | | 2x+4(x−2)=40 | | 5-3x+2(4x-3)=14 | | -10-u=4u+10 | | b/3-16=-14 | | -2(5x+10)=-80 | | −4+w+17−2/3w=16 | | 2(x-3)-x-4=15 | | -5-8w=2w+5 | | 3p+8-5p=20 | | 6w-8=5w-9 | | 43+5(d−4)= | | 7x-1=x-8 | | 8=7e | | (x+6)^3=-27 | | -4c+12+11c=-37 | | 2x-5(x-3)=2(x-10) | | x-1/7=4 | | -22+-11x=98 | | 8q+3=9q | | 17.99+76m=179.11 | | 50+6x=30+9x | | -8-5n=63 |

Equations solver categories